The awareness of the HPV vaccines in female students of secondary school and in their parents - Kowalczyk-Amico, Katarzyna; Suzin, Jacek; Bladowska, Katarzyna; Janas, Anna (Polish Journal of Public Health, 2010)
Introduction. According to the latest data in Poland cervical cancer is the fifth most common cancer in women as well as the seventh cause of death considering cancer mortality rates. Clinical studies on the bivalent vaccine in the group of women who have not initiated sexual cohabitation, clearly reveal reducing the risk of CIN III by 87%, however in Poland such procedure is still not common. Aims. 1. Assess the state of knowledge of the vaccines against HPV in female adolescents attending third class of secondary school and in their parents 2. Analyse of main arguments against the HPV vaccinations indicated by 16-year-old secondary school students and their parents. 3. Assess the sources and access to information on vaccination against HPV virus. Materials and methods. In February and March 2010 the survey containing 14 questions (mainly yes/no type) was conducted among 200 female adolescents attending the third class of public secondary school. A similar, appropriately modified questionnaire was directed to the parents of these students (200 questionnaires as well). Results. Ultimately, 183 valid questionnaires were received from girls and 164 from their parents. In the group of female adolescents only 28.89% and 23.89% heard of the HPV virus and HPV’s transmission route respectively. Almost 74% would undergo the vaccination against HPV if it was free of charge; the remaining 26% of them refuse, due to the total lack of information about this procedure. Gynecologist informed 0.55% of the respondents about the possibility of vaccination; similarly, GP informed only 0.67% of the surveyed females. Sexual cohabitation was not initiated by 91.01% of the questioned females, which clearly qualifies them for vaccination. Main causes of not vaccinating female adolescents indicated by their parents are insufficient financial resources, lack of information about the benefits, effectiveness and safety of the vaccine. Only 17.07% of the questioned parents received information about the vaccination against HPV from their GP or gynecologist. Conclusion. The level of knowledge about HPV and its role in development of cervical cancer is low. Apart from the cost of vaccination, the main cause of failing such prevention, indicated both by parents and their daughters, is lack of knowledge in the area of safety, the mechanism of action and the effectiveness of the vaccine. Neither gynecologists nor GPs participate, in a satisfactory way, in the process of sharing necessary information.